Was the 2024 US election truly a landslide win for Donald Trump? - Siraki, Ted (2025)
The 2024 US election was quickly described as a “landslide”, a label that has more recently been impugned. Most analyses, however, have not delved into the historical context and data before 2020. Doing so reveals a broader, more nuanced picture that demonstrates the significance of Donald Trump’s win and the virtual impracticability of Kamala Harris’ task.